Novel microscalpels for removing proximal composite resin overhangs on class II restorations - Wolff, Diana; Schick, Simona-Georgiana; Frese, Cornelia; Staehle, Hans Jörg (Operative dentistry, 2017)
Clinical Relevance Microscalpels and scalpel numbers 12 and 15 can be efficiently used to remove excess composite material in accessible interproximal areas. Scalpels seem to be able to cut composite resin in a material-specific manner without damaging tooth surfaces or resin material surfaces.
Gesehen am 08.10.2018